Выражение cos(π/3-α)+cos (π/3+α)-cosα 40 ​и формула по которой решали

yuliana080704 yuliana080704    3   06.06.2019 09:36    1

Ответы
AlexeyB96 AlexeyB96  06.07.2020 16:07

Решение во вложенном файле.

ПОКАЗАТЬ ОТВЕТЫ
vb8515401 vb8515401  06.07.2020 16:07

cosa+cosb=2cos((a+b)/2)cos((a-b)/2)

Пошаговое объяснение:

cos(Π/3-α)+cos (Π/3+α)-cosα=

=2cos((Π/3-α+Π/3+α)/2)cos((Π/3-α-Π/3-α)/2) -cosa=

=2cos(п/3)cosa - cosa=2(1/2)-cosa=cosa-cosa=0


Выражение cos(π/3-α)+cos (π/3+α)-cosα 40 ​и формула по которой решали
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика